The Cultivating Philanthropic Character Through the Project to Strengthen Pancasila Student Profiles at Rahmat Plus Middle School: - - Subandiyantoro; Hasbi, Muchamad Hasbi Al Haikal, S.Pd, M.Pd; Al Haikal, Muchamad Hasbi; Chosiati, Tetty; Najiburrahman, Aminudin; Maria Ulfa, Hanna; Aziaztuti, Dyah (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2022)
Implementation of the Independent Curriculum (IKM) in education units provides changes in methods, content, to educational achievement standards. At IKM, the implementation of learning through structured projects in order to get the character of Pancasila students is also an educational innovation that simultaneously changes educational activities in schools. Strengthening the profile of Pancasila students which is carried out through project learning or often known through P5 (Project for Strengthening Pancasila Student Profiles) is a breakthrough which is expected to be able to develop educational outputs, namely students with character. SMP Plus Rahmat as one of the schools that implements IKM and P5 also carries out projects that are oriented towards cultivating students' philanthropic character. The project activities were carried out in collaboration with the Bustanul Amri Mosque, the Genius Yatim Mandiri Project, and the Project Team, hereinafter referred to as the Rahmat Plus Middle School Service Team. The activity was carried out using an experiential learning approach which was attended by 59 grade 8 students at SMP Plus Rahmat. It is hoped that through this activity students will be able to gain meaningful experiences that can improve students' philanthropic characteristics.